QTL Mapping and Candidate Gene Screening for Enhancing Oil Content in Silage Maize - Jianzhong Wu; Qi Wang; Weibo Han; Qian Zhao; Dequan Sun; Zhongbao Shen (Plants)
Assessing the nutritional quality of silage maize (Zea mays L.) hinges largely on its oil content, a complex quantitative trait influenced by multiple genes. Mining candidate genes within oil content-related quantitative trait loci (QTLs) can provide genetic resources and a theoretical foundation for cultivating high-oil silage maize varieties. This study employed 274 doubled haploid (DH) lines derived from the parental lines BY4944 and DNF34-2 to perform main gene plus polygene mixed genetic analysis and complex interval mapping (CIM), with the goal of pinpointing oil content-related QTLs and genes distributed across the Z. mays L. genome. Leveraging 5400 single nucleotide polymorphism (SNPs), a high-resolution silage maize genetic linkage map covering 3864.51 cM was constructed with an average interval between markers of 0.74 cM. Analysis of the map revealed 13 oil content-related QTLs. The most significant large-effect QTL (qOIL-1-1), located on chromosome 1 within the region spanning 240.93 Mb to 256.57 Mb, exhibited a logarithm of odds (LOD) score of 3.34 and explained 5.06% of oil content-related phenotypic variation. Within these QTLs, 617 genes were annotated. Through transcriptome analysis combined with quantitative real-time polymerase chain reaction (RT-qPCR), five candidate genes potentially associated with oil content were predicted and subsequently validated within these genetic loci. This research underscores the potential of identifying candidate genes to enhance breeding efforts aimed at augmenting oil content, thereby advancing animal husbandry practices.